2020
DOI: 10.3389/fpsyt.2020.00152
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Antipsychotic Drugs in Pediatric Patients: Data From a 1-Year Naturalistic Study

Abstract: Background: Antipsychotic drugs (APs) are increasingly used to treat a variety of psychiatric disorders in children and adolescents. However, their safety and tolerability profiles, when used in a developmental age context, show different characteristics from the ones observed in adult patients. Treatment with APs in pediatric patients is often long-term. However, the tolerability data regarding these patients mostly derive from short-term studies.Methods: Starting from April 2017, for a 1-year period, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…A possible explanation for our findings could be that the standardized safety measuresincluding TDM with specialist diagnostic interpretation and recommendation -carried out as part of the study could have had a preventive effect on the development of serious ADRs under off-label conditions and could also have contributed to their most favorable course. In our study, a higher proportion of serious ADRs had a positive outcome than in the naturalistic studies cited above, in which (mostly non-serious) ADRs observed in youth during antipsychotic pharmacotherapy fully recovered in 27 % and improved in 24 % of cases [49], or fully recovered in 17.6 % and improved in 38.2 % of cases [50]. Unfortunately, no separate information about the outcome of serious ADRs was provided in either of these studies.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…A possible explanation for our findings could be that the standardized safety measuresincluding TDM with specialist diagnostic interpretation and recommendation -carried out as part of the study could have had a preventive effect on the development of serious ADRs under off-label conditions and could also have contributed to their most favorable course. In our study, a higher proportion of serious ADRs had a positive outcome than in the naturalistic studies cited above, in which (mostly non-serious) ADRs observed in youth during antipsychotic pharmacotherapy fully recovered in 27 % and improved in 24 % of cases [49], or fully recovered in 17.6 % and improved in 38.2 % of cases [50]. Unfortunately, no separate information about the outcome of serious ADRs was provided in either of these studies.…”
Section: Discussioncontrasting
confidence: 71%
“…Another prospective study on the safety of antipsychotics in children and adolescents classified 10.1 % of the ADRs recorded under naturalistic conditions as serious, which were observed in 5.7 % of patients, and of which one third were psychiatric effects [75]. These authors point out, that concerning psychiatric ADRs, it is difficult to assign causality to psychotropic drugs with high reliability because of a potential worsening of the underlying condition and thus insufficient treatment effects [50]. The most common 'adverse event' in our study -'suicidality' -is at the same time a typical symptom of depression, which was the most frequent diagnosis in the sample and is known to be a strong risk factor for suicide [51].…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, however, the use of methylphenidate or atomoxetine was avoided as these medications may add further to the potential burden of adverse effects and their use is off-label in very young children. The main side effects noted for risperidone and aripiprazole were weight gain (30%) and asymptomatic elevated prolactin (20%), which have been noted in previous studies [ 11 , 19 , 69 ].…”
Section: Discussionsupporting
confidence: 56%
“…A recent large-scale systematic meta-review showed that both treatments presented an increased risk for weight gain in children and adolescents ( Solmi et al, 2020 ). In this regard, there has been an increase in evidence comparing the effects of these 2 antipsychotics on these populations in recent years ( Ishitobi et al, 2013 ; Wink et al, 2014 ; Nicol et al, 2018 ; Schoemakers et al, 2019 ; Cicala et al, 2020 ). Head-to-head comparison studies between aripiprazole and risperidone in these populations showed similar results on weight gain and lipid/glycemic parameters, in both the short term (6–12 weeks) ( Ishitobi et al, 2013 ; Nicol et al, 2018 ) and long-term (1 year) ( Wink et al, 2014 ; Schoemakers et al, 2019 ; Cicala et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%